AN UNREAL STORY OF A REAL DREAM (Dream as a "second reality" in the short story "Burial in Sushic" by Petar Saric) (Heritage, 2020)
Although his life is tied to the Kosovo-Metohian environment, the greatest living writer from Serbia's southern province, Petar Saric, with his thematic motifs, stayed faithful to the Banians, that have almost a mythical appearance in his novels. After immense suffering and pogrom of Serbs from Kosovo and Metohy in 1999, Saric has stayed faithful to the spiritual space, and his exile from Prishtina, where he has lived and worked for years, didn't mean an exile from the southern Serbian province. Finding refuge in a seemingly more quiet and safer place, in Strpce, on Brezovica, Saric practically chooses not to be defeated in his personal life and literature. It is witnessed by his works published after the ominous year at the end of the millennium. But life in a hostile environment, a constant fear of revenge and death, has made Saric turn to "realistic prose." However, it has been realistic only when the tragic everyday life has become a subject of the art process, where another layer has been added, typical for Saric's narrative act, and it can be described as magical, enigmatic, and phantasmagoric, as an intertwining of realistic and unrealistic, physics and metaphysics.The story "Funeral in Sushic" (2015) is, above all, characterized by a moral lesson of a story about a dream that is more horrifying than reality and reality that is more horrifying than a dream; other words, it is characterized by a function of a dream in the story. On the one hand, it enabled the writer to present the readers with everyday life reality through a different "reality" - the reality of a dream (since most vivid dreams are often more persuasive than the moments of "reality"); it enabled him to involve a reader into the magical world of storytelling and narration through a story of the evil that was spread through spaces of reality and spaces of dreams. On the other hand, "Funeral in Sushic" is realized as a universal story of man's suffering, that is a suffering of any man in any time, where a dream of one's own death was used as a "base" for a story about "a man in adversity and a soul in agony" (Goethe). The most profound meaning of the story is in its narrative rhetorical question "is it possible that I will give a eulogy to myself!" With this question, Saric not only opened new dimensions of meaning and values of his mainly realistic prose, but he raised the following question: Isn't it that we deliver the eulogies for ourselves and to ourselves, where the spaces of evil in his prose become hopeless distances of life, especially in a place of an ordeal and in a time of ordeal like the one that the writer brings into his story: 2015, Strbac, Brezovica (Kosovo and Metohy).
Keywords: Petar Saric,